(untitled) (Annals of Medical Research, 2022)
Aim: Obstructive sleep apnea (OSA) is a syndrome that causes complete or partial cessation of breathing and as a result of several pathways, hypertension (HT), type 2 diabetes mellitus (DM), and hyperlipidemia (HL) are usually seen as comorbidities. The main problem in the literature is, due to the presence of some confounders, especially body mass index (BMI), it is still not clear that if OSA is an independent risk factor for these comorbidities. This issue may be shown more clearly with BMI and age-matched subjects since they are strongly related to metabolic diseases and HT. Comparison of the ratios of the presence of DM, HL, and hypertension between the age and BMI matched groups is primarily aimed in the present study to see if moderate and severe OSA could be an independent risk factor for these comorbidities. Materials and Methods: Patients admitted with sleep problems were retrospectively scanned from the patient files and cases with polysomnography and routine blood test were included. The body mass indexes, ages, smoking, and alcohol habits of the cases were noted. Two groups were formed based on polysomnography, taking a threshold value of the apnea-hypopnea index (AHI) of 15. Group 1 had cases with AHI <15 (normal and mild apnea patients) and Group 2 had cases with AHI≥15 (moderate/severe apnea patients). Subjects were accepted as having DM, HL, or HT if they are on medication or if their examination and/or laboratory results show the presence of these diseases. The ratios of these diseases within the groups were compared. Numerical variables were given as mean±standard deviation. Categorical variables were shown as a number. Categorical variables were tested with the Chi-Square test or Fisher’s exact test and an independent T-test was used for two independent groups. Statistical significance was accepted as p<0.05. Results: There were 22 cases with an AHI<15 and 17 cases with an AHI ≥15, with similar mean BMI and age (p= 0.206, p= 0.054 respectively). The ratio of hypertension was found significantly higher in moderate/severe OSA patients (47% vs 5%; p=0.005). On the other hand, the ratios of DM and HL were found statistically similar (p=0.49, p=1.0 respectively). Conclusion: This study aimed to show the possible independent role of sleep apnea in metabolic diseases and HT, by creating two groups with similar BMI, age, and cigarette and alcohol habits. The results support moderate/Severe OSA as an independent risk factor for hypertension, while DM and HL are thought to be in close relationship with BMI.